PENGEMBANGAN PERANGKAT PENILAIAN LITERASI SAINS BERORIENTASI PROGRAMME FOR INTERNATIONAL STUDENT ASSESSMENT (PISA) - Widiyanti, Ifa Seftia Rakhma; Winata, Anggun; Cacik, Sri (Universitas Nahdatul Ulama Surabaya, 2017)
The general objective of this study was to find a kind of evaluation instrument for scientific literacy oriented toward Programme for International Student Assessment (PISA) and the specific purposes of this study were to investigate the validity, effectiveness, and practicality of it. This was a Research & Development study which was simplified into two stages; they are the preliminary stage and the development stage. This study resulted of multiple choice test which the validity was 3,35. The instrument was very effective to be used by students and science concept lectures in Elementary School Education Programmed to describe the profile of scientific literacy. The instrument could practically be used by the students and science concept lecturers in Elementary School Education Programmed based on the positive students and lecturers‟ responses.